First Substitute x=-1 into the equation 4[tex] x^{2} [/tex] + 3[tex] y^{3} [/tex] = 28, and you get y=2.
Take the derivative of the equation 4[tex] x^{2} [/tex] + 3[tex] y^{3} [/tex] = 28, using implicit differentiation:
8x + 9[tex] y^{2} [/tex][tex] \frac{dy}{dx} [/tex] = 0
Rearrange this in terms of [tex] \frac{dy}{dx} [/tex]:
[tex] \frac{dy}{dx} = - \frac{8x}{9y^{2} } [/tex]
Keep in mind that [tex] \frac{dy}{dx} [/tex] is equal to [tex] \frac{ \frac{dy}{dt} }{ \frac{dx}{dt} } [/tex]
Substitute and you will get the following:
[tex] \frac{ \frac{dy}{dt} }{ \frac{dx}{dt} } = - \frac{8x}{9y^{2} }[/tex]
Put in the values for x, y, and [tex] \frac{dy}{dt} [/tex] and solve:
[tex]\frac{ \frac{dy}{dt} }{ \frac{dx}{dt} } = - \frac{8x}{9y^{2} }[/tex]
[tex]\frac{8}{ \frac{dx}{dt} } = \frac{8}{36}
[/tex]
[tex] \frac{dx}{dt} = 36[/tex]